PERTIMBANGAN HAKIM MEMUTUS BEBAS TINDAK PENGANIAYAAN PASAL 351 (1) KUHP (PUTUSAN NO: 301/PID.B/2020/PN.SBG) - Azra Sulaiman; Vience Ratna Multiwijaya (Reformasi Hukum Trisakti, 2022)
The high level of heavy persecution occurs for various reasons, including the desire to get something, lack of social control in society, problems that cause hostility between perpetrators and victims, individuals who cannot control their emotions, prejudice against others, humiliated or harassed and feeling betrayed by the perpetrator. The problems in this research are whether the defendant's actions is in accordance with the elements in Article 351 paragraph (1) of the Criminal Code or not and what is the judge's verdict for the perpetrators of the crime of persecution? (Court Decision Number 301/Pid.B/2020/PN Sbg). To answer the problems, the research conducted in normative and descriptive analytical legal research by using secondary data. The conclusions: the verdict was the defendant was acquitted, meaning the decision is not having a deterrent effect on the defendant. Based on the analysis of the subject matter, it should be in the judge's consideration that it was proven that the defendant commited the crime and the judge should give a sentencing decision and the defendant should have been sentenced guilty that the defendant committed the crime of persecution under Article 351 paragraph (1) of the Criminal Code.